Statistical analysis of the Tigris River water and drinking water in some locations of Mosul - Luay Mohammad Fadhil Alimam; Mahmood Khalil Saleem; Ghazi AbdulHadi Aliraqi (College of Education for Pure Sciences, 2013)
Abstract Tigris river has considered as a major source of water in Iraq. This river affected by industrial and domestic waste water passing through Mosul city. And to study the quality of Tigris river and its suitability for drink in Mosul city, The selected samples contain two types of water (raw, supplied(, Four areas near four water projected (New left, Old left, Opraway an Hammam Alaleel). The samples were taken for four seasons (Winter-January, Spring-April, Summer-July and Autumn-October) and replied two times at statistical analysis, The total number of samples were (64). The PH value, Calcium, Magnesium, Chloride, Sulfate, Total Hardness, Alkalinity and Electrical Conductivity were measured according to international standard methods in analyses. The quality of Tigris river water in Mosul city region with the supplied water has been estimated for the drinking water and humanity according to international and European standards. After the analyses of samples a high significant effect was noticed on calcium, However, Interaction of the water types with water projects locations and seasons was noticed on many tests, but no any effects were found on others. The value of tests has not changed in the two types of water (raw and supplied) in the case of Magnesium, Chloride, Sulfate, Alkalinity, and Electrical Conductivity. All tests were agreed with the international standard qualities.